2001
DOI: 10.1046/j.1471-4159.2001.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proteasome inhibition on cellular oxidative damage, antioxidant defences and nitric oxide production

Abstract: The ubiquitin/proteasome pathway plays an essential role in protein turnover in vivo, and contributes to removal of oxidatively damaged proteins. We examined the effects of proteasome inhibition on viability, oxidative damage and antioxidant defences in NT-2 and SK-N-MC cell lines. The selective proteasome inhibitor, lactacystin (1 microM) caused little loss of viability, but led to significant increases in levels of oxidative protein damage (measured as protein carbonyls), ubiquitinated proteins, lipid peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
95
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 44 publications
24
95
0
2
Order By: Relevance
“…Overall, our data support the growing view that proteasomal dysfunction may be a significant contributor to neuronal cell death in the major neurodegenerative diseases (18,28,52,53,55). Our data shown that abnormal proteins such as mutated Parkins impact on the ubiquitin-proteasome system, leading to oxidative stress and excess NO production.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Overall, our data support the growing view that proteasomal dysfunction may be a significant contributor to neuronal cell death in the major neurodegenerative diseases (18,28,52,53,55). Our data shown that abnormal proteins such as mutated Parkins impact on the ubiquitin-proteasome system, leading to oxidative stress and excess NO production.…”
Section: Discussionsupporting
confidence: 86%
“…The mutant proteins could elevate levels of NO 2 Ϫ /NO 3 Ϫ , for which increased expression of nNOS (but not iNOS) was presumably responsible. Again, such effects have been observed in cells treated with proteasomal inhibitors (55). However, the mutant proteins did not decrease proteasomal hydrolytic activities; rather they were increased although the increase with wild-type Parkin was greater than for the mutants (as measured using substrates whose hydrolysis is not ubiquitin-dependent).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…L'inhibition des activités du protéasome par des substances spécifiques (type lactacystine) induit une agrégation et une oxydation des protéines cellulaires non dégradées [13]. Ces agrégats sont constitués de protéines en fin de vie qui s'accumulent dans la cellule sous forme ubiquitinylée [14]. L'inhibition du protéasome s'accompagne également de la synthèse de Hsp70, dans un phénomène qui représente probablement une réponse Bag-1 Cochaperon déstabilisant la forme ATP du complexe Hsc70/Hsp70-substrat Tableau I. Principales protéines chaperons impliquées dans la réponse cellulaire au choc thermique.…”
Section: Concept De Chaperons Moléculairesunclassified